2005
DOI: 10.1038/sj.jcbfm.9600074
|View full text |Cite
|
Sign up to set email alerts
|

Initial Oligemia with Capillary Flow Stop Followed by Hyperemia during K+-Induced Cortical Spreading Depression in Rats

Abstract: Local cerebral blood volume (CBV) and capillary flow changes in regions of depolarizing neurons during K þ -induced cortical spreading depression (CSD) in the cerebral cortex of a-chloraloseurethane-anesthetized rats were examined employing a transillumination (550 nm) video system. Capillary flow was calculated as the reciprocal of mean transit times of blood in pixels of 40 lm  40 lm, each of which contains a few capillaries. Potassium microinjection into the cortex evoked repetitive wave-ring spreads of ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 25 publications
7
40
0
Order By: Relevance
“…Under nonphysiologic conditions, such as systemic hypoxia and reduced cerebral perfusion pressure, the vasoconstrictive response can be augmented and become the predominant response to CSD, as previously reported in response to CSD during focal and global ischemia (Shin et al, 2006;Sonn and Mayevsky, 2000;Strong et al, 2007). The observed variability of hypoperfusion response to CSD in previous studies (Ayata et al, 2004;Bures and Buresova, 1956;Duckrow, 1993;Fabricius et al, 1995;Farkas et al, 2007;Lauritzen, 1987;Mayevsky et al, 1998;Osada et al, 2006;Piper et al, 1991;Sonn and Mayevsky, 2000;Tomita et al, 2002Tomita et al, , 2005Van Harreveld and Stamm, 1952;Van Harreveld and Ochs, 1957) may thus be related to differences in baseline systemic physiology (pO 2 , BP), choice of anesthesia, species, and the caliber of vessels from which the recordings are obtained.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Under nonphysiologic conditions, such as systemic hypoxia and reduced cerebral perfusion pressure, the vasoconstrictive response can be augmented and become the predominant response to CSD, as previously reported in response to CSD during focal and global ischemia (Shin et al, 2006;Sonn and Mayevsky, 2000;Strong et al, 2007). The observed variability of hypoperfusion response to CSD in previous studies (Ayata et al, 2004;Bures and Buresova, 1956;Duckrow, 1993;Fabricius et al, 1995;Farkas et al, 2007;Lauritzen, 1987;Mayevsky et al, 1998;Osada et al, 2006;Piper et al, 1991;Sonn and Mayevsky, 2000;Tomita et al, 2002Tomita et al, , 2005Van Harreveld and Stamm, 1952;Van Harreveld and Ochs, 1957) may thus be related to differences in baseline systemic physiology (pO 2 , BP), choice of anesthesia, species, and the caliber of vessels from which the recordings are obtained.…”
Section: Discussionmentioning
confidence: 56%
“…*P < 0.01 versus normoxic normotension and hypoxic normotension; w P < 0.01 versus normoxic normotension. Under normoxic normotensive conditions, the characteristic large hyperemia is often preceded by a small hypoperfusion, as previously described in anesthetized rats, rabbits, and cats (Ayata et al, 2004;Fabricius et al, 1995;Osada et al, 2006;Tomita et al, 2002Tomita et al, , 2005Van Harreveld and Stamm, 1952), suggesting that CSD causes vasoconstriction followed by vasodilation. More recently, selective measurements of arterial diameter in 15-to 25-day-old rats show heterogeneous vasomotor responses to CSD depending on the vessel caliber.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…When neuronal-vascular coupling is so prevented, the stimulus-induced P O2 decrease ('dip') is enhanced and prolonged, resembling in vitro conditions [59]. In the case of SD, hyperemia predominates while neurons are depolarized but this is usually followed by prolonged hypo-perfusion [72][73][74][75][76][77][78]. The late hypo-perfusion following SD can cause delayed reduction of NADH-NAD + [44].…”
Section: Oxygen Availability -Resolving the Discrepancy Between In VImentioning
confidence: 99%
“…Recently, astrocytic calcium has been linked to motion of vessels (Zonta et al, 2003;Filosa et al, 2004;Mulligan and MacVicar, 2004;Metea and Newman, 2006); the astrocytic wave of SD could therefore affect blood flow (Mulligan and MacVicar, 2004). Several laser Doppler flowmetry (LDF) studies observed that, occasionally in rats Dreier et al, 2001;Ayata et al, 2004;Tomita et al, 2005) and mice (Ayata et al, 2004), a brief hypoperfusion precedes the large transient hyperemia in SD. This can become a deleterious ischemia when nitric oxide is blocked or extracellular [K ϩ ] is artificially elevated (Dreier et al, 2001).…”
Section: Introductionmentioning
confidence: 99%